TECHNICAL EFFICIENCY ANALYSIS OF SUPERIOR RICE FARMING USING THE DIRECT SEED PLANTING METHOD IN PADDY FIELDS OF KUSAN TENGAH SUB-DISTRICT, TANAH BUMBU DISTRICT, INDONESIA - Zulkipli; Yanti N.D.; Ferrianta Y. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
This study aims to analyze the influence of the use of factors of production on the production of superior rice farming, the level of technical efficiency and the factors causing inefficiency in the Tablea method of superior rice farming techniques. The results of the analysis show that the production factors that have a significant effect on the production of superior rice using the Tablea method are the production factors of large areas of land, seeds, fertilizers, liquid medicine and labor. The value of the technical efficiency index of rice farming using the Tablea method is 0.9262. Factors causing technical inefficiency in rice farming using the Tablea method are the age of the farmer, the education level of the farmer and the farmer's length of experience in farming.